2020
DOI: 10.1016/j.conbuildmat.2020.121276
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous shrinkage of slag-fly ash blends activated with hybrid sodium silicate and sodium sulfate at different curing temperatures

Abstract: The autogenous shrinkage increased with increasing the concentration of sodium sulfate solutions. Increasing curing temperature decreased the autogenous shrinkage of AASF systems. The S ions provided by the activating solutions have limited influence on the reaction process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 63 publications
1
6
0
1
Order By: Relevance
“…The effect of higher amounts of GGBS in alkali-activated GGBS/fly ash is to decrease the setting time as shown in Figure 6(a) and (b), which is consistent with the literature [27]. The fast setting time associated with the presence of GGBS may be addressed in various ways, such as the addition of up to 2% microsilica [29]. Borax may also be used to increase setting time [42].…”
Section: Effect Of Naoh Molarity On Initial Setting (Is) and Final Setting (Fs) Timessupporting
confidence: 83%
See 2 more Smart Citations
“…The effect of higher amounts of GGBS in alkali-activated GGBS/fly ash is to decrease the setting time as shown in Figure 6(a) and (b), which is consistent with the literature [27]. The fast setting time associated with the presence of GGBS may be addressed in various ways, such as the addition of up to 2% microsilica [29]. Borax may also be used to increase setting time [42].…”
Section: Effect Of Naoh Molarity On Initial Setting (Is) and Final Setting (Fs) Timessupporting
confidence: 83%
“…Calcium is abundant in GGBS precursor in the form of CaO. The fast dissolution of Al and Si, in addition to abundance of calcium, modifies the network and forms reaction products at faster rate [29].…”
Section: Effect Of Naoh Molarity On Initial Setting (Is) and Final Setting (Fs) Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the large variety in the precursors and activators that are used in these systems 5–7 . The complexity is further increased with the variation in the physical and chemical properties of the precursors, blending of different precursors 8,9 and using different compositions of activators 10,11 . Although this makes AAM systems challenging to analyze, the variability present in component and composition choices increases the flexibility for customizing the final product in line with specific project requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Uppalapati et al 38 demonstrated that increasing Na 2 O content from 1.75 to 2.75% increases the 1-, 3-, 7-, and 28-day compressive strength of GGBS + fly ash (GGBS/fly ash = 80%/20% by volume) mortars, activated using a mixture of sodium silicate and sodium sulfate solutions. Similarly, increasing the curing temperature from 20 to 40 °C also consistently increases the compressive strength at each of the curing days.…”
Section: Introductionmentioning
confidence: 99%